ГЕОГРАФИЯ САБАҚЛАРЫН ОҚЫТЫЎДА ӨЗБЕТИНШЕ ТАПСЫРМАЛАРДЫ ПАЙДАЛАНЫЎДЫҢ ӘҲМИЙЕТИ - Жиемуратова, Г.Ө.; Ходжаева, Г.А. (ILIM hám JÁMIYET, 2020)
This article is about the importanse of using methods of individual work for develoving creative thinking of secondary schools pupils.